PENDEKATAN SOSIAL DALAM PENELITIAN KESEHATAN REPRODUKSI - Rosalia Sciortino (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1995)
Population problems, particularly fertility and family planning program, used to be approached from a clinical instead of socio-culture perspectives. A clinical point of view never involves through aspect of reproductive right thought; which includes the right of any individuals (men and women) and couples (husband-wife) in making decisions in terms of reproductive behaviour along their reproductive ages. In this regard, this paper states that reproductive healthproblems should be understood from a social perspective. This is because reproductive health problems is cause and influence social, political,and economic system as well as gender relation. Therefore, the selection of the appropriate social - cultural research methods/approaches is undoubtedly needed. Methodology should be developed appropriately to meet the research goals and objectives.